WEB as part of a multimodality treatment in complex, large, and partially thrombosed intracranial aneurysms: a single-center observational study of technical success, safety, and recurrence. (22nd January 2016) - Kabbasch, C; Mpotsaris, A; Reiner, M; Liebig, T
Abstract : Introduction: Complex, large, wide-neck aneurysms, but particularly partially thrombosed intracranial aneurysms (PTIAs), have a greater tendency to recanalize after coil occlusion. The Woven Endovascular Bridge (WEB) combines shape memory wires braided to a relatively uniform, dense surface, which may limit its compaction and its incorporation into an existing aneurysm clot and may thus reduce PTIA recurrence. Objective: To carry out a retrospective analysis of our experience with the WEB as part of a complex treatment in conjunction with other implants to assess the efficacy and safety of this technique. Methods: Among 43 aneurysms treated with the WEB in our center, eight complex, large, wide-neck aneurysms were treated in conjunction with other implants (additional WEBs, coils, stents, flow diverters). Six of these eight aneurysms were PTIAs. All patients were followed up by DSA between 3½ and 38 months. Results: All eight (100%) of the complex, large, wide-neck aneurysms were treated successfully and without periprocedural adverse events (0%). At follow-up, the two non-thrombosed aneurysms were completely occluded, but all six PTIAs recurred (75%) and were re-treated. There was no morbidity or mortality in these eight patients. Conclusions: Treatment of large, complex aneurysms with the WEB in conjunction with other implants was technically successful and safe but did not prevent recurrence of partially thrombosed aneurysms in our center. PTIA re-treatment was possible and not limited by the previously placed WEB.